The Effectiveness of Academic Supervision in Improving Online Learning during the Covid-19 Pandemic - Fadhilah Fadhilah; Murniati Murniati; Nasir Usman (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to determine the implementation of the principal's academic supervision based on the implementation program, supervision, supporting and inhibiting factors in online learning during the covid-19 period at a state junior high school in  Pidie Jaya. The data collection techniques used were observation, interview, and documentation study. The research subjects were school principals and teachers, totalling 12 respondents. The data analysis used was reduction techniques, data presentation, data interpretation and data verification. The results showed (1)The planning of the principal's academic supervision is carried out by establishing cooperation between teachers, principals and related parties for the achievement of learning quality. (2) The implementation of the principal's academic supervision is carried out by observing teachers doing online learning through competency standards, basic competencies, success indicators, and teaching materials. In addition, the presentation of fun material, the use of appropriate methods, and the presence of media are integrated indicators to determine the success of learning. (3) The existence of teacher awareness, good teacher perceptions, and support from parents to students are supporting factors for academic supervision so that the implementation runs successfully during the covid-19 pandemic.